Single and repetitive low-velocity impact responses of sandwich composite structures with different skin and core considerations : A review - Ahmad Kueh, Beng Hong; Saddam H., Abo Sabah; Diyar N., Qader; Siti Hasyyati, Drahman; Mugahed, Amran (Elsevier Ltd., 2023)
Sandwich structures are fast becoming prevalent in engineering fields due to their maximal stiffness coupled with minimal mass. However, additional to the commonly examined impact responses, which are more threatening versus those of static, the highly destructive repetitive impact loading is the more realistic condition evident in applications. Also, numerous failure modes have been observed but not well characterized for the sandwich structural configurations. This article, therefore, reviews the recent research advancements in the responses of sandwich structures subjected to low-velocity impact under both single and repetitive loading cases. The definitions of low-velocity impact are first discussed to provide the scope of this review, i.e., described as ≤ 100 m/s by different sources. The general impact performance metrics are then presented with the prospect of introducing an overall impact behavior appraisal by combining these terms into one non-dimensional index as recently published. Additionally, the paper offers an outlook on the common failure modes of sandwich structures, the relevant mode maps for failure type identification, and the factors that influence the structural responses under lowvelocity impact. The main influencing factors of low-velocity impact responses comprise facesheet and core geometrical and material configurations, impactor characteristics, hydrothermal effects, and support conditions while less affected by the loading rate. Facesheet or core crushing, facesheet or core buckling, and delamination have been identified as the main failure modes regardless of due to single or repetitive impact, with indentation, penetration, and perforation being more central to the latter. Besides, several good practices for the typically employed finite element approach for investigating sandwich structures under low-velocity impact are summarized and recommended. To underline, the parametric ranges covered in this review include applied impact energies of 0.06 – 360 J, impact velocities of 0.5 – 34.2 m/s, with repeated impact numbers up to 400 times, resulting in absorption energies of 0.01 – 396.3 J, and the determined.